Empowering Interior Design Students and Local Communities through Task-Based Language Teaching (TBLT) - Agung Krsna Lila Dasa; Wicaksana, GDA (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
This study examines the impact of Task-Based Language Teaching (TBLT) on improving speaking comprehension among 23 interior design students at Institut Desain dan Bisnis Bali (IDB Bali). Using a Classroom Action Research (CAR) approach based on Kemmis and McTaggart’s model, students participated in two learning cycles, where they engaged in online speaking tasks submitted via Google Drive. Speaking performance was evaluated across five key indicators: fluency, pronunciation, vocabulary, grammar, and comprehension. The results indicate a 3.3% improvement in speaking comprehension from Cycle 1 to Cycle 2, with fluency and pronunciation showing the most significant gains. These findings confirm that TBLT, combined with digital submission methods, enhances students' ability to communicate effectively in professional settings. Beyond academic outcomes, this study highlights the potential of TBLT as a tool for community-based training, particularly in supporting local creative industries. By equipping students with effective communication skills, this approach can improve client interactions, business negotiations, and cross-cultural collaborations in interior design and related fields. Future research should explore the long-term impact of TBLT and its integration into industry-driven language training programs.